2007
DOI: 10.1590/s0101-20612007000500015
|View full text |Cite
|
Sign up to set email alerts
|

Produção de inóculo do cogumelo comestível Pleurotus pulmonarius (Fr.) Quélet - CCB19 a partir de resíduos da agroindústria

Abstract: ResumoOs cogumelos comestíveis são muito apreciados pelo sabor e qualidades nutricionais. Resíduos lignocelulósicos da agroindústria são excelentes substratos tanto para sua produção como para propagação do micélio (inóculo ou semente). O objetivo deste trabalho foi avaliar três resíduos oriundos do processamento de alimentos, palha de arroz (PA), sabugo de milho (SM) e casca de amendoim (CA) para produção de inóculo de Pleurotus pulmonarius CCB19. As sementes foram posteriormente inoculadas em sacos contendo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 10 publications
1
4
0
5
Order By: Relevance
“…However, the addition of wheat flour with 5 or 10% mushroom powder reduced the sugar content, but it did not increase the fat content, remaining similar to the flour without Pleurotus sajor-caju had 48.4% yield (Experiment 3 - Table 2), similar to the results found for P. ostreatus (46.67%) banana straw (Furlan et al, 2008), and P. pulmonarius (43%) in corn straw (Oliveira et al, 2007). Biological efficiency values varying from 4.08 to 5.03% were found in literature (Bhatti et al, 2007;Holtz et al, 2009;Furlan et al, 2008), values that are similar to those found in this study (4.5%).…”
Section: Analysessupporting
confidence: 80%
“…However, the addition of wheat flour with 5 or 10% mushroom powder reduced the sugar content, but it did not increase the fat content, remaining similar to the flour without Pleurotus sajor-caju had 48.4% yield (Experiment 3 - Table 2), similar to the results found for P. ostreatus (46.67%) banana straw (Furlan et al, 2008), and P. pulmonarius (43%) in corn straw (Oliveira et al, 2007). Biological efficiency values varying from 4.08 to 5.03% were found in literature (Bhatti et al, 2007;Holtz et al, 2009;Furlan et al, 2008), values that are similar to those found in this study (4.5%).…”
Section: Analysessupporting
confidence: 80%
“…The biological efficiency (EB), production rate (TP) and productivity (P) of P. ostreatoroseus DPUA 1720 were 22.90, 54.33 and 3.55% in CE+RB (800 g: 200 g), 60% humidity in dry basis, respectively. Close values were obtained by Oliveira et al (2007) using peanut bark to produce P. pulmonarius. The biological efficiency was around 23% and productivity was 4.58%.…”
Section: Resultsmentioning
confidence: 93%
“…Low values of biological efficiency can be explained by the organism genetics, culture conditions, substrates composition and its proportion used in the process. Besides, the biological efficiency can interfere in environmental factors as temperature, humidity, luminosity and pH (Oliveira et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A produção de inóculo de P. pulmonarius também foi avaliada em cascas de amendoim, sabugo de milho e palha de arroz (OLIVEIRA et al, 2007), bem como a produção de basidiomas de P. sajorcaju em substratos à base de casca de café, palha e sabugo de milho, ou da palha do feijoeiro (DIAS et al, 2003). A palha de arroz, folhas de bananeira, capim-elefante também foram citados por Obodai, Cleland-Okine e Vowotor (2003) para o cultivo do P. ostreatus.…”
Section: Introductionunclassified